2018
DOI: 10.1080/17538157.2018.1433676
|View full text |Cite
|
Sign up to set email alerts
|

Predicting treatment outcome of drug-susceptible tuberculosis patients using machine-learning models

Abstract: Tuberculosis (TB) is a deadly contagious disease and a serious global health problem. It is curable but due to its lengthy treatment process, a patient is likely to leave the treatment incomplete, leading to a more lethal, drug resistant form of disease. The World Health Organization (WHO) propagates Directly Observed Therapy Short-course (DOTS) as an effective way to stop the spread of TB in communities with a high burden. But DOTS also adds a significant burden on the financial feasibility of the program. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 20 publications
0
25
0
Order By: Relevance
“…This approach has also been used at health facilities to predict disease severity in patients with dengue fever 20 and malaria, 39 and children with acute infections. 40 Researchers have used this approach to quantify the risk of tuberculosis treatment failure 41 and assess the risk of cognitive sequelae after malaria infection in children. 42 See Online for appendix…”
Section: Ai-driven Interventions For Healthmentioning
confidence: 99%
“…This approach has also been used at health facilities to predict disease severity in patients with dengue fever 20 and malaria, 39 and children with acute infections. 40 Researchers have used this approach to quantify the risk of tuberculosis treatment failure 41 and assess the risk of cognitive sequelae after malaria infection in children. 42 See Online for appendix…”
Section: Ai-driven Interventions For Healthmentioning
confidence: 99%
“…It is important to note that Peetluk et al [23] do not classify LR as machine learning in their review as the LR analysis was used as a statistical methodology to understand the relationship between attributes and their prevalence. In the few machine learning studies identified, it was used primarily for predicting treatment completion [39] or unfavourable outcomes [40,41].…”
Section: Related Workmentioning
confidence: 99%
“…Hussain and Junejo [39] propose and evaluate three machine learning models-SVM, RF and Neural Network (NN). Their data set comprised 4213 records from an unidentified location; 64.37% of the records represented completed treatments.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations